2015
DOI: 10.1007/s00436-015-4520-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined Serological Detection of Circulating Angiostrongylus vasorum Antigen and Parasite-specific Antibodies in Dogs from Hungary

Abstract: The occurrence of the nematode Angiostrongylus vasorum, also known as the French heartworm, is increasingly being reported from various European countries. The adults of this parasite species live in the pulmonary arteries and right cardiac ventricle of wild canids and domestic dogs. Larval stages and eggs in the lungs induce inflammatory verminous pneumonia, causing severe respiratory disease in dogs. Furthermore, haematological and neurological signs and even death may occur. In Hungary, A. vasorum has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…With 0.66 % of the examined dogs being positive in both ELISAs, the prevalence in Portugal is apparently higher than that found for Germany (Schnyder et al 2013a ) or Poland (Schnyder et al 2013b ) and lower than in Hungary (Schnyder et al 2015a ), UK (Schnyder et al 2013a ) and Italy (Guardone et al 2013 ), but not significantly. Nevertheless, it is important to highlight that this study surveyed shelter dogs, i.e., stray dogs usually not under any kind of prophylaxis and therefore frequently demonstrating higher parasitic prevalence (Alho et al 2014 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…With 0.66 % of the examined dogs being positive in both ELISAs, the prevalence in Portugal is apparently higher than that found for Germany (Schnyder et al 2013a ) or Poland (Schnyder et al 2013b ) and lower than in Hungary (Schnyder et al 2015a ), UK (Schnyder et al 2013a ) and Italy (Guardone et al 2013 ), but not significantly. Nevertheless, it is important to highlight that this study surveyed shelter dogs, i.e., stray dogs usually not under any kind of prophylaxis and therefore frequently demonstrating higher parasitic prevalence (Alho et al 2014 ).…”
Section: Discussionmentioning
confidence: 76%
“…Regarding the geographical distribution of A. vasorum , southern France (Guilhon and Cens 1969 ; Bourdeau 1993 ), south-east England and Wales (Jacobs and Prole 1975 ; Simpson and Neal 1982 ) and Denmark (Bolt et al 1992 ) were traditionally considered areas with high endemic foci, while sporadic cases were diagnosed all over Europe. Nowadays, A. vasorum has a very heterogeneous distribution with reports suggesting the presence of endemic hotspots in many areas, namely in Croatia (Rajkovic-Janje et al 2002 ), Italy (Della Santa et al 2002 ; Guardone et al 2013 ), Switzerland (Staebler et al 2005 ), Germany (Staebler et al 2005 ; Barutzki and Schaper 2009 ), Spain (Segovia et al 2004 ; Mañas et al 2005 ), Greece (Papazahariadou et al 2007 ), Poland (Demiaszkiewicz et al 2014 ), Slovakia (Miterpakova et al 2014 ), Hungary (Schnyder et al 2015a ) and others. Several hypotheses have been raised to explain this possible expansion, such as increased movements of pet dogs and increased fox populations even in urban areas, suggesting that new areas are open to colonisation (Morgan et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the present investigations dogs from two municipalities, Pančevo and Gornji Milanovac, should be considered to be at a high risk of angiostrongylosis. Currently, canine angiostrongylosis is endemic in many areas of Europe (Elsheikha et al, 2014), and in neighbouring Hungary, for instance, Schnyder et al (2015) found 1.36% Angiostrongylus antibody-and antigenpositivity in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…However, only in the last two decades, infections with this latter parasite, residing in the heart and pulmonary arteries in the adult stage, have been recorded in a massively increasing number of European countries out from the traditional endemic foci in France (Guilhon 1963) or Ireland (Dodd 1973). Very recent reports from Eastern European countries describe the presence of the parasite in Hungary (Schnyder et al 2015b;Tolnai et al 2015), Croatia (Rajkovic-Janje et al 2002) and also from countries surrounding the Czech Republic. Germany, bordering northwesterly, is the one with long-standing reports of A. vasorum cases (Pallaske 1967;Eckert and Lämmler 1972) and several epidemiological studies confirmed its presence in particular in the south-eastern part of Germany (Taubert et al 2008;Barutzki and Schaper 2009;Schnyder et al 2013a).…”
mentioning
confidence: 99%